Preoperative pulmonary rehabilitation for marginal-function lung cancer patients. (January 2017) - Hashmi, Asra; Baciewicz, Frank A; Soubani, Ayman O; Gadgeel, Shirish M
Background: This study aimed to evaluate the impact of preoperative pulmonary rehabilitation in lung cancer patients undergoing pulmonary resection surgery with marginal lung function. Methods: Short-term outcomes of 42 patients with forced expiratory volume in 1 s < 1.6 L who underwent lung resection between 01/2006 and 12/2010 were reviewed retrospectively. They were divided into group A (no preoperative pulmonary rehabilitation) and group B (receiving pulmonary rehabilitation). In group B, a second set of pulmonary function tests was obtained. Results: There were no significant differences in terms of sex, age, race, pathologic stage, operative procedure, or smoking years. Mean forced expiratory volume in 1 s and diffusing capacity for carbon monoxide in group A was 1.40 ± 0.22 L and 10.28 ± 2.64 g∙dL −1 vs. 1.39 ± 0.13 L and 10.75 ± 2.08 g∙dL −1 in group B. Group B showed significant improvement in forced expiratory volume in 1 s from 1.39 ± 0.13 to 1.55 ± 0.06 L ( p  = 0.02). Mean intensive care unit stay was 6 ± 5 days in group A vs. 9 ± 9 days in group B ( p  = 0.22). Mean hospital stay was 10 ± 4 days in group A vs. 14 ± 9 days in group B ( p  = 0.31). There was no significant difference in morbidity or mortality between groups. Conclusion: Preoperative pulmonary rehabilitation can significantly improve forced expiratory volume in 1 s in some marginal patients undergoing lung cancer resection. However, it does not improve length of stay, morbidity, or mortality.